1992
DOI: 10.1063/1.106503
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of light-emitting porous Si

Abstract: Characterization of light-emitting porous Si films with x-ray photoelectron spectroscopy is reported. Only traces of O are detected on HF-etched samples, in contradiction to an earlier report that oxides are a significant component of porous Si. Si 2p and valence-band measurements demonstrate that the near-surface region of high porosity films which exhibit visible luminescence consists of amorphous Si.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(45 citation statements)
references
References 19 publications
2
43
0
Order By: Relevance
“…( 1) i.e., the SHG anisotropy is consistent with a C2v symmetry of the nonlinear tensor ^ (2).n This symmetry of the macro scopic nonlinear response is the same as the approximate microscopic symmetry observed with AFM. This correlation between macroscopic and microscopic symmetry was also observed for the ''soft'' surface: the mea sured SHG response from these surfaces was essentially iso tropic, just as there was also no observable structure in the AFM scans.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…( 1) i.e., the SHG anisotropy is consistent with a C2v symmetry of the nonlinear tensor ^ (2).n This symmetry of the macro scopic nonlinear response is the same as the approximate microscopic symmetry observed with AFM. This correlation between macroscopic and microscopic symmetry was also observed for the ''soft'' surface: the mea sured SHG response from these surfaces was essentially iso tropic, just as there was also no observable structure in the AFM scans.…”
supporting
confidence: 51%
“…4). Equation (2) suggests that the oscillatory behavior in the observed time dependence is the result of an interference effect. This can be attributed to the fact that due to the growth of the PS layer, the SHG intensity shows interference maxima and minima due to multiple reflections between the air-PS and the PS-Si interfaces.…”
mentioning
confidence: 99%
“…d. Structurally disordered phases: A significant amount of amorphous silicon was reported to contain within porous silicon (Perez et al, 1992). It is known that hydrogenated amorphous silicon (a-Si:H) can produce visible PL (Vasquez, 1985) and so it was suggested that a-Si:H might be responsible for 'red' PL band (Vasquez et al 1992) The observed tunability of the PL was further suggested as due to introduction of hydrogen into the amorphous silicon in varying amounts (Cullis & Canham,1991).…”
Section: Photoluminescencementioning
confidence: 99%
“…Chemical etching of silicon using chemical solutions of HF, HNO 3 and water (Vasquez et al, 1992), NaNO 2 and HF or CrO 3 and HF (Beale et al, 1986;Zubko et al 1999) are employed for PS formation. However, the most widely used method is the electrochemical etching of silicon crystal in an electrolyte solution of HF and ethanol or methanol (Saha et al, 1998;Kanungo et al, 2006) or HF and water or HF and N, N dimethyl formamide (DMF) (Archer et al, 2005) by passing current for a fixed duration of time.…”
Section: Preparation Of Nanocrystalline Porous Silicon Using Differenmentioning
confidence: 99%
“…[1][2][3][4][5] However, other studies support different mechanisms of luminescence: several experimental and theoretical papers claimed [6][7][8] that both the quantum confinement and the surface ͑hydrogen saturation͒ effects are responsible; Brandt et al 9 suggested that it may be attributable to a Si-backbone polymer, such as Si 6 O 3 H 6 ͑some later studies 10,11 also supported a similar idea͒; Xu, Gal, and Gross 12 assigned luminescence to molecules attached to the Si surface; a few authors attributed it to hydrogen-related surface species such as SiH 2 and polysilanes; 13,14 the formation of amorphous silicon has also been considered as a possible luminescent mechanism. 15 Some recent papers 16 -18 are very helpful in understanding the origin of the visible luminescence.…”
mentioning
confidence: 99%